PENGARUH DIVERSIFIKASI DAN INSIDER OWNERSHIP TERHADAP CORPORATE GOVERNANCE DAN NILAI PERUSAHAAN - Sastrodiharjo, Istianingsih (Jurnal Akuntansi, 2018)
The objective of this study is to examine the effect of diversification and insider ownership on firm value. The sample used in this study is 95 firm's annual reporting from companies listed in Jakarta Stock Exchange in 2015. Structural Equation Approach used in this study to examine the effect of diversification and the other variable together on the firm value and the corporate governance.The results of this study show that diversification significantly affects the insider ownership. Furthermore, business diversification negatively significant affects the firm value. On the other hand, I find no evidence of the effect of diversification on the corporate governance index. The result of this study is different from the previous study in another country. The different result may be caused by the different international corporate governance practice.